Analysis of students’ learning difficulties in the virus material for class X at SMAN 1 Klaten - Virbiarsari, Ervika Thania; Subiantoro, Agung Wijaya (Universitas Negeri Yogyakarta, 2026)
This study aims to: (1) Determine students’ learning difficulties in class X virus material; (2) To find out the factors that cause students’ learning difficulties in the biology subject of virus material class X at SMAN 1 Klaten; (3) To find out what efforts can be made to overcome students’ learning difficulties in class X virus material at SMAN 1 Klaten. This research is a descriptive qualitative study. The research design focuses on the exploration and in-depth understanding of the factors that cause learning difficulties and the efforts to overcome them. This research was conducted at SMAN 1 Klaten, with research subjects comprising class X students and class X biology teachers. The research instruments used are interview and questionnaire guidelines, which have undergone validity and reliability testing to ensure the accuracy and consistency of the data. The interview data analysis technique used the Miles and Huberman model, and the questionnaire analysis technique used descriptive statistics. The results of this study show that students have difficulty learning viral material biology due to a lack of interest in the subject. To overcome these learning difficulties, students seek information online. The results of this study confirm the importance of developing more contextual, interactive, and technology-based learning strategies to increase students’ interest and engagement in learning about the virus.